Tourism and monarchy in Vietnam - Nguyen, Pham Hung (H. : ĐHQGHN, 2019)
Early forms of tourism began to appear under the feudal autonomy in Vietnam from the mid-tenth century, after the country's independence from China, to the mid-nineteenth century, before Vietnam became a French colony. Due to its specific characteristics of history, Vietnam had no proper tourism activities, including tourism services and products, travel routes, tourists and a tourism market, and these have been defined in modern times. However, they did present some similarities with what we would now describe as touristic activities. Vietnam’s tourism in the feudal period was closely related to popular “tourism activities” combined with the official business of the royal court, which can be understood as "MICE2 tours" today. Under the policy of "trọng nông ức thương" (agriculture promoted but trade not encouraged), the closed-door policy (bế quan tỏa cảng) of the imperial court, as well as the common social views popular among ordinary people, tourism was not seen as an economic activity. Rather it was regarded as a cultural activity. Nevertheless, without these formal activities, many precious cultural heritages would not have been preserved; many famous scenic spots would not have been discovered and honoured as they are today. In other words, tourism during the feudal period has endowed the next generations with many tourist attractions and resources, contributing to the development of tourism in Vietnam today. In this paper some representative cases are used to illustrate these activities and their roles in tourism development in modern Vietnam.